Determinan Hasil Pemeriksaan HPV DNA pada Wanita Usia Subur di Puskesmas Kasihan II - Heni Indriani; Evi Wahyuntari (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Cervical cancer ranks among the most common cancers and is a primary contributor to female mortality worldwide, especially in countries with lower and middle-income economies, such as Indonesia. A lasting infection with human papillomavirus (HPV), especially the cancer-causing types HPV-16 and HPV-18, significantly increases the risk of developing cervical cancer. A positive HPV DNA test result indicates a high risk of cervical cell transformation into precancerous lesions and invasive cancer, making HPV DNA testing an important indicator for assessing cervical cancer risk. Therefore, HPV DNA detection serves as a key indicator for identifying the risk of developing cervical cancer. This study aims to describe the determinants of HPV DNA test results among women of reproductive age at Puskesmas (Community Health Center) Kasihan II, Bantul Regency. This study employed a descriptive quantitative design with a cross-sectional approach. The sample consisted of 48 women of reproductive age who underwent HPV DNA testing and were selected using a purposive sampling technique. Secondary data were obtained from medical records and included age at first marriage, smoking habits, number of sexual partners, family history of cervical cancer, parity, and use of hormonal contraception. Data were analyzed using frequency distributions. The results showed that the majority of respondents were HPV-negative across variables such as age at first marriage, smoking habits, number of sexual partners, family history, parity, and hormonal contraception use. However, both negative and positive results require careful attention through strengthened routine screening and reproductive health education as preventive measures against cervical cancer in primary healthcare settings.